SINGKATAN DAN AKRONIM DALAM SURAT KABAR: KAJIAN BENTUK DAN PROSES - Noviatri Noviatri (JURNAL ARBITRER, 2015)
The reason for choosing abbreviation as the object of research is motivated by the phenomenon of widespread and high usage of abbreviation in the community, especially in the newspaper. In addition, based on the process of formation, the abbreviation used in many newspapers are not consistent with the general process of abraviation. In terms formation the abreviation in newspaper are not follow the rules of abreviation formation which violated the grammar of Bahasa Indonesia. The theory used in this research is the theory of abbreviation and formation process proposed by Kridalaksana (2010) which divides abreviation into five types, 1) abreviation, 2) acronym, 3) beheading, 4) contraction, and 5) symbol of letter. Results of the data analysis whows there are 1562 (one thousand five hundred and sixty-two) abbreviation in the newspaper with 9 (nine) processes, including three of them are new process (research findings) and 896 (eight hundred and ninety-six) acronymy used in newspapers with 31 (thirty-one) process and 19 pieces are employed new process. Thus, based on formation process of abbreviations and acronyms there are 22 (twenty-two) new processes.